PENGARUH KUALITAS PELAYANAN PEMBUKAAN REKENING SECARA MOBILE (BYOND) DAN MANUAL TERHADAP KEPUASAN NASABAH PADA PT BANK SYARIAH INDONESIA Tbk KCP BOGOR KOTA WISATA - Gusti Setiawan; Irwin Sukrisno Sugeng; Andri Rizko Yulianto (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to determine the effect of mobile account opening (BYOND) and manual service quality on customer satisfaction at PT Bank Syariah Indonesia Tbk, Bogor Kota Wisata Branch. The study used quantitative methods, with a sample of 171 respondents selected from a population of 300 customers. Data was collected through questionnaires and analyzed using SPSS version 26. The results show that mobile account opening (BYOND) service quality has a positive and significant effect on customer satisfaction, with t-value of 5.277 and significance of 0.000. Manual account opening service quality also has a positive and significant effect on customer satisfaction, with t-value of 4.493 and significance of 0.000. Simultaneously, both variables significantly influence customer satisfaction, with F-value of 132.124 and significance of 0.000. The coefficient of determination (R²) of 0.611 indicates that 61.1% of customer satisfaction variation is explained by both variables.